Association of human papillomavirus with prÃ¦invasive and invasive cervical carcinoma - Nurhayati, Z. A.; Yadav, M.; Daniels, J. M.; Norhanom, A.W. (Malaysian Journal of Science, 2017)
Several human papillomavirus (HPV) types have been implicated in the development of cervical carcinoma worldwide. The use of molecular techniques have facilitated the detection and typing of HPV in cervical lesions. Seventy four formalin-fixed tissues of various cervical lesions were analysed by in situ hybridization using digoxigenin-labelled probes for HPV 16 and 18 DNA sequences. HPV DNA was found in 76% of the cervical tissues. The prevalence of HPV DNA sequences increased with severity of the CIN lesions ranging from in CIN 1 and in CIN 2 to in CIN 3/CIS. HPV DNA was detected in 80% of both adenocarcinoma and squamous cell carcinoma cases. Analysis of the data by viral type revealed that 1--1PV 16 prevailed in 25% of CIN 1, of CIN 2, 55% of CN 3/ CIS, 20% of adenocarcinomas and 67% of squamous cell carcinomas. HPV 18 was detected ofCRâ€¢.1 1, ofCm 2, of CIN 3/CIS, 80% of adenocarcinomas and 67% of squamous cell carcinomas. The detection rate of HPV DNA increased from 25% in low grade lesions (CIN 1) to 77% in high grade lesions (CIN 2 and CIN 3/CIS). In squamous cell carcinoma 16 DNA was prevalent as frequently aOHPV 18 DNA but in adenocarcinoma HPV 18 DNA was detected more often than HPV 16 DNA. Mixed infections with both HPV types occurred more often than single infections with either type. The increasing association of HPV 16 and 18 with enhanced severity of the precursor lesions suggests that these high risk oncogenic viruses may have a role in the development and progression of cervical cancer.